Words, images and gender: Lessons from a survey on the public perception of synthetic biology and related disciplines - Porcar, Manuel (EMBO Rep, 2019)
A large survey of visitors at a science museum about the perception of biotechnology shows that names matter and that gender has an influence on people's attitude towards new technologies.[Image: see text]